Betaphycus gelatinus and B. philippinensis (Gigartinales, Rhodophyta) are conspecific - Dumilag, Richard V. (Phytotaxa, 2018)
Due to lack of definitive differences in phenotypic characters, earlier taxonomic work questioned the separation between Betaphycus gelatinus and B. philippinensis. To date, no attempt has been made to clarify their species boundaries. To investigate whether the two names constitute distinct species, an organellar marker-based phylogenetic approach (rbcL, COI-5P, and cox2-3 spacer) was performed using molecular species discrimination methods (ABGD, SPN, GMYC, and PTP/bPTP). Concordant with observed and published morphological data, the molecular results revealed that B. gelatinus is indistinguishable from B. philippinensis. The name B. philippinensis is thus relegated to synonymy with B. gelatinus.